2001
DOI: 10.1016/s0968-8080(01)90098-9
|View full text |Cite
|
Sign up to set email alerts
|

Including expectant fathers in antenatal education programmes in Istanbul, Turkey

Abstract: In this article we present the results of three studies investigating methods for including men in antenatal education in Istanbul, Turkey. Participants were first-time expectant parents living in low and middle-income areas. After a formative study on the roles of various family members in health during the period surrounding a first birth, an antenatal-clinic-based education programme for women and for couples was carried out as a randomised, controlled study. Based on the results, separate community-based a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 13 publications
3
37
0
1
Order By: Relevance
“…Our analysis confirms findings from other studies demonstrating that many men are interested in increased involvement in maternal and child health and that men already engage in some positive behaviors [8, 30, 31]. We found that many men embrace the importance of newborn care and that some already go against deeply entrenched cultural norms to carry out healthy practices such as exclusive breastfeeding, institutional delivery and joint decision making with their partners.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our analysis confirms findings from other studies demonstrating that many men are interested in increased involvement in maternal and child health and that men already engage in some positive behaviors [8, 30, 31]. We found that many men embrace the importance of newborn care and that some already go against deeply entrenched cultural norms to carry out healthy practices such as exclusive breastfeeding, institutional delivery and joint decision making with their partners.…”
Section: Discussionsupporting
confidence: 89%
“…a Compiled from findings of other authors [8, 12, 19, 21, 23, 30, 31, 37, 38] as well as this secondary analysis.…”
Section: Discussionmentioning
confidence: 97%
“…The dependency on women to invite men for male involvement in maternal health care indicates lack of readiness by the health care sector to invest in community based approaches that have proved successful elsewhere [29]. In this study, the health care providers in the MCH department were often overburdened with their work.…”
Section: Discussionmentioning
confidence: 97%
“…Men’s involvement in ANC is also intended to encourage husbands to support women’s care from pregnancy, to delivery, and throughout the postnatal period [1]. Research suggests that men’s presence during ANC can improve uptake of institutional deliveries [23], postnatal service utilization [24], and spousal communication [25]. However, socio-cultural norms that define pregnancy as a woman’s domain as well as health systems factors such as poor health worker communication and low male representation among staff have been shown to discourage men’s participation [11, 26].…”
Section: Introductionmentioning
confidence: 99%